Debunking the myth: usage of thiamine in cervical preparation and labour augmentation - A. Z. Suryawan; A. Sh. Nisa; D.P.J. Santoso; S. A. Slamet; B. Handono (Акушерство, гинекология и репродукция)
In Indonesia, thiamine (B1) has been use for cervical priming and enhancing uterine contraction in midwife and hospital setting as its off-label effect. However there are no clear evidence and research related to this issue. Thiamine itself was founded in 1990’s and has been used extensively as labour augmentation in 1940–1960’s. Main hypothesis previously due to B1 increased function of the uterine body and lower uterine segment obliteration during labour which also responsible for the reduction of pain. Thiamine also assumed to promote stimulation of uterine contractions by direct participation in nerve impulses that regulates and establish the rhythm of uterine contractions and also inhibits action of cholinesterase which reduce acetylcholine clearance. However recent research proves B1 mainly function in Krebs cycle specifically in decarboxylase of pyruvate to acetyl-CoA in form of thiamin diphosphate, synonymously known as thiamine pyrophosphate. Due to clear foundings of B1 function in cell energy metabolism, study of B1 in labour augmentation was not continue further. It’s also related to uterine contraction function in labour not relied on it’s paracervical parasympathetic ganglia which respond to acetylcholine but rely heavily on oxytocin and its receptor. As conclusion, the author stated B1 have no effect on labour progression however could prove beneficial if the mother has B1 deficiency as it’s could reduce energy output from cell which could affect myometrial contraction.